Poles apart? EU enlargement and the labour market outcomes of immigrants in the UK - Stephen Drinkwater; John Eade; Michal Garapich (Institute for the Study of Labor (IZA), 2006)
The UK was one of only three countries to allow migrants from accession countries to enter their labour markets more or less without restriction following EU enlargement in May 2004. Therefore, it is important to establish the characteristics and labour market performance of migrants from these countries who have subsequently entered the UK. We principally analyse Labour Force Survey data to compare the labour market outcomes of recent migrants from Poland and other accession countries to those of earlier migrant cohorts from these countries as well as to those of other recent migrants to the UK. We find that the majority of post-enlargement migrants from accession countries have found employment in low paying jobs, despite some (especially Poles) having relatively high levels of education. It follows that recent Polish migrants typically have lower returns to their education than other recent arrivals. Migrants from the new entrants who arrived immediately prior to enlargement possess similar characteristics and labour market outcomes, apart from having a higher propensity to be self-employed. These results are discussed in the context of policy changes, migration strategies, assimilation effects and possible impacts on the sending countries.
urn:nbn:de:101:1-20090309199
Keywords: 330